Camouflage during movement in the European cuttlefish (Sepia officinalis) - Josef, N. (2018)
A moving object is considered conspicuous because of the movement itself. When moving from one background to another, even dynamic camouflage experts such as cephalopods should sacrifice their extraordinary camouflage. Therefore, minimizing detection at this stage is crucial and highly beneficial. In this study, we describe a background-matching mechanism during movement, which aids the cuttlefish to downplay its presence throughout movement. In situ behavioural experiments using video and image analysis, revealed a delayed, sigmoidal, colour-changing mechanism during movement of Sepia officinalis across uniform black and grey backgrounds. This is a first important step in understanding dynamic camouflage during movement, and this new behavioural mechanism may be incorporated and applied to any dynamic camouflaging animal or man-made system on the move.